Someone to hold [large type] - Balogh, Mary (Balogh, Mary. Westcott novel, 2017)
Camille Westcott, who has been declared illegitimate and without a title, moves to Bath to teach at an orphanage, where she meets artist Joel Cunningham, for whom she feels a mutual contempt until things take a passionate turn.